Diversity of Soil Insects on Hiking Trails in the Forest of Mount Prau - Muthiati, Aisyaah; Indriyanti, Dyah Rini; Widiyaningrum, Priyantini; Abdullah, Muhammad (Life Science, 2025)
Soil insects are insects that carry out all their activities in or on the soil surface. Soil insects play a vital role as decomposers, predators, herbivores, and soil structure improvers. This study aims to investigate the diversity of soil insects along the hiking trails of Mount Prau with varying levels of hiking intensity, namely the Patak Banteng trail with high intensity, Dwarawati with moderate intensity, and Purwosari with low intensity. The method used was the pitfall trap, with a total of 120 traps installed along the three trails. Insect identification was conducted in the laboratory using a stereo microscope, and environmental factors such as temperature, humidity, soil pH, light intensity, organic carbon (C) content, nitrogen (N), phosphorus (P), and soil texture were measured as supporting data. The results showed 20 soil insect species from 6 orders and 11 families, with a total of 445 individuals. The order Coleoptera was dominant in all plots, particularly the species Xantholinus sp. (Staphylinidae). The highest Shannon-Wiener diversity index was found in the Dwarawati plot (H’=1.90), followed by Purwosari (H’=1.82), and the lowest in Patak Banteng (H’=1.59). High evenness (E) values (>0.6) and low dominance (D) values.